The Impact of Floating Population on Public Utility Management: A Case Study of Rangsit University Students in Muang Ake Village, Pathum Thani Province - Nasen, Weerapap; Jewjinda, Chanchai (Journal of Dhamma for Life, 2025)
This research aimed to achieve three main objectives: 1) to investigate the problems arising from the increase of floating population in the Rangsit University area, 2) to study the impacts of the floating population on the administration and management of Rangsit City Municipality, and 3) to explore potential solutions to various problems resulting from the influx of floating students at Rangsit University. This qualitative research employed an in-depth interview methodology, collecting data from a purposive sample of 15 individuals. The sample consisted of 10 community leaders from Muang Ek Village and 5 administrators from Rangsit University. The findings reveal that the growth of the floating population, predominantly Rangsit University students, has led to severe challenges in fundamental public utilities within Muang Ek Village. Key issues include overflowing waste bins, insufficient water pressure, power outages/fluctuations, and congestion in public transportation systems. Furthermore, this phenomenon significantly impacts the administration and management of Rangsit City Municipality. The municipality faces an increased workload that disproportionately exceeds its allocated budget and personnel, which are primarily based on inaccurate registered population data. This discrepancy compromises the efficiency of public service planning and delivery. The municipality also grapples with challenges in local revenue collection, along with broader issues related to infrastructure and environmental degradation, such as damaged roads and wastewater management.